Reproductive ecology of Baer's Pochard Aythya baeri in south China - Wei, Sai; Jia, Hui; Chen, Yawen; Pan, Wuyuan; Chen, Yuyan; Lu, Qun; Tao, Xudong; Ding, Changqing; Lu, Xin (Wildfowl, 2020)
Baer's Pochard Aythya baeri is an IUCN Critically Endangered diving duck, but our lack of knowledge of its reproductive ecology impedes implementation of effective conservation actions. We therefore report on the results of studies of the birds’ breeding biology at a subtropical site in south China, well south of the traditionally recognised breeding range of this species. Here the Baer's Pochard depended on undisturbed wetlands with emergent vegetation as breeding habitat, where they nested in shallow water or on platforms above local water levels. Egg laying occurred between late April and mid-July. Clutch size averaged 9.7 eggs (range: 5–14), with evidence of conspecific parasitism being found in 29% of 31 nests. Incubation lasted for 24 days (range: 23–26), after which at least one fledged young was recorded for 38% of 45 nesting attempts (41% estimated by the Mayfield method), a success level comparable with several less endangered Aythya species. Nesting failure was attributed to nest desertion, possibly associated with warm weather, nest predation by Siberian Weasels Mustela sibirica and flooding. Based on these results, we propose that the protection of at least 120 ha of continuous wetland as breeding habitat, with management of emergent vegetation adjacent to open water, and provision of artificial nest-site microhabitats (e.g. nesting platforms), will all potentially enhance the breeding success of this species.